EVALUATING THE POSIBILITY OF APPLYING QUALITY MANAGEMENT SYSTEM IN AGRICULTURAL PRODUCTS - Vesić, Dobrica (Economics of Agriculture, 2005)
Management is an integral part of modern economy. The universal character of management concept is confirmed by its application in such complex activity as agricultural production. Quality Management System (QMS) is a comprehensive business concept aimed at process management. The main approach to the QMS concept is the process approach. From the viewpoint of the QMS application in agrikultural production, the process is related to identifying managing and improving the production process according to the customers' needs, wishes, requirements and expectations.